Prevalence and Predictors of Urinary Tract Infections among Children with Cerebral Palsy in Makurdi, Nigeria - Emmanuel Adémólá Anígilájé; Terkaa Terrumun Bitto (International Journal of Nephrology)
Background. Children with cerebral palsy (CP) are prone to urinary tract infection (UTI). Methods/Objectives. The prevalence and the predictors of UTI among children with CP were compared to age- and sex-matched children without CP at Federal Medical Centre, Makurdi, Nigeria, from December 2011 to May 2013. Results. The age range was between 2 and 15 years with a mean age of years including 30 males and 22 females. UTI was confirmed in 20 (38.5%) CP children compared to 2 children (3.8%) without CP ( value 0.000). Among CP children, Escherichia coli was the commonest organism isolated in 9 (9/20, 45.0%), Streptococcus faecalis in 4 (20.0%), and Staphylococcus aureus in 3 (15%), while both Proteus spp. and Klebsiella spp. were isolated in 2 children (10.0%) each. Escherichia coli was also found in the 2 children without CP. All the organisms were resistant to cotrimoxazole, nalidixic acid, nitrofurantoin, and amoxiclav, while they were 100% sensitive to ceftriaxone and the quinolones. In a univariate regression analysis, only moderate to severe gross motor dysfunction predicted the risk of UTI (, 95% CI, 2.27–1324.00, value 0.014). Conclusion. Efforts should be put in place to aid mobility among CP children in order to reduce the risk of UTI.